AN INVENTORY PLANNING AND CONTROL ANALYSED USING ECONOMIC ORDER QUANTITY (EOQ) AND PERIOD ORDER QUANTITY (POQ) METHODS AT UD. MARIADI RANGKA - Abdul Aziz Syarif; Yetti Meuthia Hasibuan; Budhi Santri Kusuma (Sean Institute, 2022)
Supplies are always needed by every company, both small companies and large inventories. With the inventory procurement policy, it is expected that the production process can run smoothly. Without an inventory of raw materials, companies are faced with the risk that one day the company will not be able to meet consumer needs. The purpose of this research isdeterminethe number of purchases of raw materials at each order with the lowest costAndknow the right time period to place an order for raw materials by forecasting the need for raw materials in the coming year, with the aim of knowing an overview of needs in the next year. The data studied is in the form of data on raw material needs, data on ordering costs, storage costs, frequency of purchasing raw materials and the number of purchases of raw materials during 2021. Data collection techniques are by way of interviews, observations.This research includes descriptive research (descriptive research). To anticipate undesirable things related to the supply of raw materials, the researcher advises the company to provide a safety stock of 20 pallets and 1 sheet of plywood and place an order again when the raw materials are1,114pallets and 27 sheets of plywood. Based on the conclusions above, the authors provide advice to companies to consider using the POQ method and determine the required raw material requirements, the amount of safety stock and when the company must place an order again so that efficient and effective inventory control can be achieved.